2015
DOI: 10.1016/j.bbadis.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

miR218-5p regulates the proliferation of gastric cancer cells by targeting TFF1 in an Erk1/2-dependent manner

Abstract: Trefoil factor 1 (TFF1), a member of the trefoil peptide family, is not only associated with mucosal protection and restoration but is also correlated with tumorigenesis of the gastrointestinal tract. In an early study, we performed sequence analysis and identified one potential miR423-5p binding site within the 3'-untranslated region of TFF1 using microRNA target prediction tools. In the current study, we demonstrated that the coding DNA region within TFF1 is also a candidate for miR218-5p targeting. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…miR-632-mimic (25 nM) and miR-632-inhibitor (50 nM) were purchased from Qiagen. The cell transfection method was described previously [28].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-632-mimic (25 nM) and miR-632-inhibitor (50 nM) were purchased from Qiagen. The cell transfection method was described previously [28].…”
Section: Methodsmentioning
confidence: 99%
“…217184) was used for miRNA extraction from GC patient serum following the manufacturer’s protocol. miRNA first-strand cDNA synthesis and real-time PCR were performed as previously described [28]. miR-632 and control primers were purchased from Qiagen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of miR-423-5p on proliferation induction and invasion inhibition may result in the decrease of TFF1 and the increase of cyclin D1, cyclin D3, and β-catenin expression which can promote the progression of GCs [26]. A recent study has demonstrated that miR218-5p restrains TFF1 in an extracellular signal-regulated kinase 1/2 (Erk1/2)-dependent manner, then motivates the proliferation of human GC cells [128]. Targeting miR218-5p may provide a novel tactic for the treatment of GC.…”
Section: Mir-504/ P53 Mir-423-5p and Mir218-5p/ Erk1/2 Signaling Patmentioning
confidence: 99%
“…ERK1/2 activation is associated with cell cycle progression, differentiation, protein translation and cell death. JNK and p38 MAPK pathways modulate cellular senescence and oncogenic transformation and play a key role in the proliferation, differentiation, survival and death of cancer cells [31,32]. JNK and p38 can have antagonist effects.…”
Section: All Induced Jnk and P38 Phosphorylationmentioning
confidence: 99%